Lignans: Advances in Biosynthesis, Bioavailability, and Pharmacological Activity - Singh, Sonia; Sharma, Shiwangi (Combinatorial Chemistry & High Throughput Screening, 2025)
Lignans, a group of naturally occurring compounds abundant in various plant-based foods, are becoming increasingly popular due to their potential health benefits. The literature suggests that these bioactive substances can reduce the risk of certain types of cancer, such as postmenopausal colon and breast cancer. Moreover, the significance of lignans for improving cardiovascular health has been recognized, as studies have revealed a potential correlation between the intake of lignans and a decreased risk of cardiovascular disease. These complex molecules possess diverse bioactive capabilities, rendering them potential alternatives for preventing chronic diseases. Further research is needed to examine the mechanisms responsible for their beneficial outcomes. Recent research has emphasized the pharmacological properties of lignans as effective substances for human health. Incorporating foods rich in lignans into the diet may be a practical approach to enhancing protection against life-threatening ailments, such as cardiovascular diseases and malignancies.
Keywords: coniferyl alcohol